Virtual World, Metaverse, and Gen Z's Social Life - Manurung, Elvy Maria; Fransiska, Federika Fransiska; Turnawan, Alfonsus Vincent (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Research on Generation Z, the latest generation who are active in the use of the Internet and smartphones, has been widely carried out. Several previous studies have shown that Gen Z as social media users who are dominated by teenagers, also experience negative impacts – in addition to the positive impacts that are for learning activities at school – because the use of smartphones dominates their daily activities. The virtual world seems more real than their real social life, with the presence of various virtual friendship applications plus the possibility of the presence of a metaverse, Gen Z's social life is believed to have moved to the virtual world. This research was conducted using a qualitative method called ethnography, in the form of document studies and interviews. This study involved 10 informants from junior and senior high school students and 2 universities in Bandung and Jakarta, West Java, Indonesia. All the transcripts were then validated by the result of interviews with teachers and parents. The results of the study show that the surrounding virtual environment can lead students to smartphone addiction. Baudrillard's concepts of simulacra and hyperreality are increasingly relevant to present and future life when virtual reality technology, i.e., metaverse, becomes part of real life. Without intense communication and attention from parents, a student can be trapped in his own virtual world and unconsciously slowly detach himself from the world of reality around him. This is proof that Gen Z’s social life today is very different from previous generations. The social life in the virtual world for Gen Z is as important as their life in the real world.